2013
DOI: 10.1364/oe.21.007050
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental validation of a three-dimensional combustion diagnostic based on tomographic chemiluminescence

Abstract: Three-dimensional (3D) measurements are highly desirable both for fundamental combustion research and practical monitoring and control of combustion systems. This work discusses a 3D diagnostic based on tomographic chemiluminescence (TC) to address this measurement need. The major contributions of this work are threefold. First, a hybrid algorithm is developed to solve the 3D TC problem. The algorithm was demonstrated in extensive tests, both numerical and experimental, to yield 3D reconstruction with high fid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(50 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…These studies require all the cameras in the same plane (co-planar). Ma et al 243,[255][256][257][258][259] modified the CT algorithms so the cameras can be located at arbitrary locations. Different algorithms such as ART algorithm and simulated annealing (SA) algorithm were selected for tomography reconstruction and flames from premixed, patterned McKenna flame ( Figure 15) to turbulent, diffusion Vshape flame (Figure 16).…”
Section: Tomography Techniquesmentioning
confidence: 99%
“…These studies require all the cameras in the same plane (co-planar). Ma et al 243,[255][256][257][258][259] modified the CT algorithms so the cameras can be located at arbitrary locations. Different algorithms such as ART algorithm and simulated annealing (SA) algorithm were selected for tomography reconstruction and flames from premixed, patterned McKenna flame ( Figure 15) to turbulent, diffusion Vshape flame (Figure 16).…”
Section: Tomography Techniquesmentioning
confidence: 99%
“…It is recognized as an important indictor in combustion diagnostics and control [1][2][3] . Compared with laser diagnostics, 3D-CTC is substantially simpler and easier to implement, also can provide information about key combustion quantities (e.g., heat release rate, local equivalence ratio) [4] , making it attractive for applications in harsh industrial environments. Chemiluminescence of flame have been studied for more than one century, and the first approach of measurement by designing a collection system to detect relatively small volume was demonstrated in 1991 [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on different imaging system, 3D-CTC can be divided into three categories [3] . The first category obtains the image projection by custom-made lens and film [8] , the second method based on lens and CCD cameras [4,9,10] , and the third method combined fiber-based endoscopes(FBEs) with multi-CCD to get the multi-direction projections [11,12] . …”
mentioning
confidence: 99%
“…The first category of techniques obtains 3D measurements by rapidly scanning a 2D technique, any 2D technique (at least conceptually) such as planar Mie scattering [4], planar laser induced incandescence [5], or even 2D absorption-based tomography [6,7]. The second category of techniques obtains 3D measurements volumetrically by performing a 3D tomography [8][9][10][11]. These two strategies have both fundamental differences (in terms of spatial resolution, temporal resolution, field of view, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Worth et al demonstrated TC as a powerful tool for resolving large scale vortex-flame dynamics by measuring mean and phased-averaged OH* distributions [17]. Cai et al investigated the performance of various tomographic algorithms and the spatial resolution of TC using stable and patterned flames [11,18,19]. Floyd et al performed phantoms studies of TC and demonstrated 3D flame measurements at tens of frames per second rate [9,15].…”
Section: Introductionmentioning
confidence: 99%